Genetic and Ecological Diversity of Escherichia coli and Cryptic Escherichia Clades in Subtropical Aquatic Environments - Koh, Xiu Pei; Shen, Zhiyong; Woo, Chun Fai; Yu, Yanping; Lun, Hau In; Cheung, Sze Wan; Kwan, Joseph Kai Cho; Lau, Stanley Chun Kwan (Frontiers in Microbiology, 2022)
Escherichia coli not only inhabit the large intestines of human and warm-blooded animals but could also persist in the external environment. However, current knowledge was largely based on host-associated strains. Moreover, cryptic Escherichia clades that were often misidentified as E. coli by conventional diagnostic methods were discovered. Failure to distinguish them from E. coli sensu stricto could lead to inaccurate conclusions about the population genetics of E. coli. Based on seven housekeeping genes, we determine the genetic and ecological diversity of E. coli and cryptic clades as they occupy aquatic habitats with different characteristics and human impact levels in subtropical Hong Kong. Contrary to previous reports, clade II was the most abundant cryptic lineage co-isolated with E. coli, being especially abundant in relatively pristine subtropical aquatic environments. The phylogenetically distinct cryptic clades and E. coli showed limited recombination and significant genetic divergence. Analyses indicated that these clade II strains were ecologically differentiated from typical E. coli; some may even represent novel environmental Escherichia clades that were closely related to the original clade II strains of faecal origins. E. coli of diverse origins exhibited clonality amidst divergent genotypes STs, echoing other studies in that recombination in housekeeping genes was insufficient to disrupt phylogenetic signals of the largely clonal E. coli. Notably, environmental E. coli were less diverse than faecal isolates despite contributed many new alleles and STs. Finally, we demonstrated that human activities influenced the distribution of E. coli and clade II in a small aquatic continuum. Moving from relatively pristine sites towards areas with higher human disturbance, the abundance of clade II isolates and new E. coli genotypes reduces, while E. coli bearing class I integrons and belonging to CCs of public health concern accumulates. Altogether, this work revealed the new genetic diversity of E. coli and cryptic clades embedded in selected subtropical aquatic habitats, especially relatively pristine sites, which will aid a more thorough understanding of the extent of their genetic and functional variations in relation to diverse habitats with varied conditions.